Perbandingan Hasil Belajar Peserta Didik Dalam Pelajaran Tahfizhul Qur’an di Qur’anic School of Dewan Dakwah Surakarta Antara Masa Pandemi dan Pasca Pandemi - Imaamah, Ummul; Ridha, Achmad Rasyid (Indonesian Journal of Islamic Educational Review, 2025)
One of the essential components and stages that teachers must take in the learning process is evaluation. A good review will provide an overview of the quality of learning, which will help teachers plan better subsequent learning strategies, and students will be able to be motivated to improve their abilities. Many educators still do not understand the nature, importance and purpose of evaluation. So, the implementation is not yet optimal. This research aims to study and research student learning outcomes in tahfizhul Qur'an lessons at the Qur'anic School of Dewan Dakwah Surakarta during the pandemic and post-pandemic. This research uses a qualitative approach, namely scientific research, that aims to understand a phenomenon in natural social contact by prioritizing a process of in-depth communication interaction between the researcher and the phenomenon to be discussed. The research location is the Qur'anic School of the Surakarta Da'wah Council, and the data collection techniques used are observation and documentation. The results of this research show that students' learning outcomes in tahfizhul Qur'an lessons at the Qur'anic School of Dewan Dakwah Surakarta after the pandemic were better than during the pandemic.